2010
DOI: 10.3109/08860221003606299
|View full text |Cite
|
Sign up to set email alerts
|

Parameters of oxidative stress and echocardiographic indexes in patients on dialysis therapy

Abstract: Aim: Quantity of oxidative stress (OS) is enhanced in every stage of chronic renal failure (CRF). OS and its effects on echocardiographic indexes in patients on hemodialysis (HD) and continuous ambulatory peritoneal dialysis (CAPD) were evaluated. Materials and methods: Thirty-nine patients on CAPD, 32 patients on HD, and 30 healthy individuals with similar demographic features were included. Patients with diabetes mellitus and chronic inflammatory diseases were excluded. Blood samples were collected to examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…In a multitude of studies, it has been found that in CRF, while MDA rises [20][21][22][23], antioxidant levels fall compared to the control group [24][25][26]. Several studies have shown that while the same findings may be observed in PD patients as well, antioxidant levels are more favorable in HD group [26,27]. It has been showed that antioxidant levels of predialysis group, on the other hand, are lower than in the control group, but higher than in HD or PD group [5,27].…”
Section: Discussionmentioning
confidence: 99%
“…In a multitude of studies, it has been found that in CRF, while MDA rises [20][21][22][23], antioxidant levels fall compared to the control group [24][25][26]. Several studies have shown that while the same findings may be observed in PD patients as well, antioxidant levels are more favorable in HD group [26,27]. It has been showed that antioxidant levels of predialysis group, on the other hand, are lower than in the control group, but higher than in HD or PD group [5,27].…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies reported conflicting results regarding MDA levels in different dialysis modalities. 22,24,27,28 These variable results may be due to some confounding factors related to the method of study of MDA. 29 Another factor which should be taken into account is that MDA is found in two forms: bound and free MDA.…”
Section: Discussionmentioning
confidence: 99%
“…Another antioxidant enzyme glutathione peroxidase (GPx) activity was determined by the coupled assay procedure of Gunzler et al 21. One unit of enzyme activity is reported as one μmol of NADPH oxidized per minute.…”
Section: Biochemical Analysis Of Parametersmentioning
confidence: 99%